Factors influencing patency of brescia-cimino arteriovenous fistulas in hemodialysis patients - Manne, Venu; Vaddi, Surya Prakash; Reddy, Vijaya Bhaskar; Dayapule, Sridhar (Saudi journal of kidney diseases and transplantation, 2017)
Autologous arteriovenous fistula is gold standard to maintain vascular access for hemodialysis patients. As per the Kidney Disease Outcomes Quality Initiative guidelines, distal veins are preferred as the first choice. In this study, a total of 134 patients and 138 fistulas were evaluated from April 2015 to March 2016. Demographic factors and clinical factors were taken into consideration. Our study showed that age, sex, diabetes, and type of construction (end-to-side vs. side-to-side) had no influence over fistula patency rates. Intradialytic hypotension was one of the risk factors for loss of fistula patency. Smoking and history of hypertension were associated with reduced patency rates (P <0.001). Primary failure was more with distal fistulas (15.2%).